2016
DOI: 10.1007/s10067-016-3419-2
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory biomarkers, disease activity index, and self-reported disability may be predictors of chronic arthritis after chikungunya infection: brief report

Abstract: The chikungunya virus (ChikV) is a reemerging mosquito-borne pathogen that causes disabling chronic arthritis. The relationship between clinical evolution and inflammatory biomarkers in patients with ChikV-induced arthritis has not been fully described. We performed a prospective case series to evaluate the association among joint involvement, self-reported disability, and inflammatory biomarkers. Patients with ChikV infection were followed for 1 year. Joint involvement and self-reported disability were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…IL‐6 is specifically expressed in the affected joints and could stimulate the release of RANKL while inhibiting the action of its decoy receptor osteoprotegerin released by osteoblasts, resulting in osteoclastogenesis and severe bone loss, as has been shown in mice . Indeed, while bone loss is not a defining feature in patients with chronic chikungunya arthritis, recent studies appear to implicate IL‐6 as a possible biomarker of chronic chikungunya virus .…”
Section: Chronic Stage Of Chikungunya Virus (>3 Months After the Onsementioning
confidence: 99%
“…IL‐6 is specifically expressed in the affected joints and could stimulate the release of RANKL while inhibiting the action of its decoy receptor osteoprotegerin released by osteoblasts, resulting in osteoclastogenesis and severe bone loss, as has been shown in mice . Indeed, while bone loss is not a defining feature in patients with chronic chikungunya arthritis, recent studies appear to implicate IL‐6 as a possible biomarker of chronic chikungunya virus .…”
Section: Chronic Stage Of Chikungunya Virus (>3 Months After the Onsementioning
confidence: 99%
“…The severity of acute CHIKV disease has previously been reported to be predictive of recovery and long-term arthritis and arthralgia symptoms [ 18 , 21 , 34 , 42 ]. Similarly in our study, several acute symptoms—including dizziness, retro-orbital pain, photosensitivity, stiff neck, sore throat, and altered mental state, which are suggestive of more severe illness—were found to be associated with increased chronic disease risk.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective Mexican cohort study showed that greater severity of acute infection predicted development of chronic arthritis, as measured by the disease activity index 28 (DAS28), World Health Organization Disablement Assessment Schedule II (WHODAS-II), and serum IL-6 level [25]. Other risk factors for chronic disease include patient age >45 years and high viral load (>10 9 per ml) during acute infection [26].…”
Section: Chronic Chikungunya Arthritismentioning
confidence: 99%